El Evangelio de Elisa Victoria (2021) y el concepto de escritura femenina - Romero Polo, Paula (Pontificia Universidad Católica del Perú, 2025)
In this article, we analyze El Evangelio (2021) by Elisa Victoria in light of the question of women’s writing, with the aim of expanding the range of issues that are normally discussed applying this concept. Toril Moi (2008) suggested that women’s writing has become a marginal topic in gender studies due to theoretical issues. After reviewing different theoretical approaches to women’s writing, we claim that the partial abandonment of this notion and the rejection it provokes in some female writers and literary critics are actually due to a misuse of this concept by feminist criticism. Seeking to address this tendency, in the second part of the article we read El Evangelio as an example of women’s writing, focusing on the novel’s interest in depicting the everyday life of its protagonist.

El presente artículo propone una lectura de El Evangelio (2021), de Elisa Victoria, a la luz de la cuestión de la escritura femenina, con la intención de ampliar el abanico de motivos que normalmente se discuten haciendo uso de este concepto. Toril Moi (2008) propuso que la escritura femenina ha quedado relegada en los estudios de género por motivos teóricos. No obstante, tras una revisión de algunas de las perspectivas teóricas acerca de la escritura femenina, concluimos que el abandono parcial de esta cuestión y el rechazo que suscita en ciertas autoras y críticas literarias responden, más bien, a un uso poco riguroso de este concepto por parte de la crítica feminista. Con el objetivo de demostrar cómo podemos corregir esta tendencia, en la segunda parte del artículo analizaremos El Evangelio como un ejemplo de escritura femenina, haciendo énfasis en el interés que muestra esta obra por describir de manera minuciosa la cotidianeidad de su protagonista.
El Evangelio by Elisa Victoria (2021) and the Concept of Women’s Writing
Keywords: Women’s writing; Feminist literary criticism; Elisa Victoria; 21st century literature; Escritura femenina; Crítica literaria feminista; Elisa Victoria; Literatura del siglo XXI; https://purl.org/pe-repo/ocde/ford#6.02.06